(3GdcTGa Yf MbGFb GdJfRjds - (3eMehO Hf YeQ Hf eMeO Hf CMeO GdNhGQRej GdReNTQqj, LGQ Gddg, CHh GdbGSe,(B538 (3g`s
(3ChdgG (B:s
(3GdMeO ddg GdPi CfRd GdbQBf cdGekG eDdakG efXekG s
(3BNQgG (B:s
(3jfJgi HBNQ JaSjQ ShQI GdeGFOI s
(3GdLRA GdChd ef fSNI CNQis
(3HChdgG hBNQgG hCKfGFgG hQjbGJ HNW MOjKs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B7 - (3U (B178 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B12 - (3U (B186 ; (3gOjI GdYGQajf ddHZOGOi(B: (3L (B2 - (3U (B402s
(3JHUQGJ GdCUd (B:s
(3GdfSNI eYGQVI Ydi fSNI GdeDpqdas
Keywords: (3GdJaSjQ hYdhe GdbQBfs